Early Genetic Mechanisms Underlying the Inhibitory Effects of Endostatin and Fumagillin on Human Endothelial Cells - Mazzanti, Chiara M.; Tandle, Anita; Lorang, Dominique; Costouros, Nick; Roberts, David; Bevilacqua, Generoso; Libutti, Steven K. (Genome Research, 2004)
A tumor needs to initiate angiogenesis in order to develop its own blood supply, to grow, to invade, and to spread. Angiogenesis, under normal conditions, is a tightly regulated balance between endogenous pro- and antiangiogenic factors. In this study, we investigated, by microarray analysis, the effects of two known antiangiogenic agents (endostatin and fumagillin) on the gene expression profiles of human umbilical vein endothelial cells (HUVEC) in order to elucidate pathways common to the effects of these agents. We observed a majority of gene expression changes within 1 and 2 h of treatment. The genes demonstrating these early expression changes are involved in cell proliferation, gene transcription, and a number have unknown functions. We selected four genes (DOC1, KLF4, TC-1, ID1) from the microarray profile that showed a similar pattern of expression for both of the antiangiogenic agents we tested. We then used small interfering RNAs (siRNA) in an attempt to better understand the role of these selected genes in the inhibitory activity of these agents. Because the gene expression changes occurred within 1 and 2 h of treatment, these genes might be involved in the initial pathways of angiogenesis inhibition.